Sustainability of the Syari’ah Economic System in Overcoming the Global Financial Crisis - Sultan Al-Qahtani; A Zulfikar Darussalam (Yayasan Adra Karima Hubbi, 2025)
Background. The global financial crisis has exposed the vulnerabilities and weaknesses of conventional financial systems, highlighting the need for alternative economic frameworks. The Islamic economic system, with its principles of risk-sharing, asset-backing, and ethical investment, offers a unique approach that contrasts with interest-based conventional systems. Islamic financial institutions operate under Shari’ah principles, which prohibit speculative transactions and excessive risk-taking, factors that have contributed to the instability of conventional systems during economic crises. Purpose. This research aims to explore the performance of Islamic financial institutions during the global financial crisis and to identify key factors that contribute to the sustainability of the Islamic economic system. The study seeks to understand how Shari’ah-based finance can provide stability and resilience in times of global economic uncertainty. Method. The research employs a case study approach, collecting data from Islamic financial institutions across several countries. Data collection techniques include in-depth interviews with industry experts, document analysis of financial reports and policies, and participatory observation within the institutions themselves. This triangulation of data ensures a comprehensive understanding of the factors contributing to sustainability. Results. The findings reveal that Islamic financial institutions experienced low Non-Performing Loan (NPL) rates and consistent positive revenue growth during the crisis. These results highlight the institutions' effective risk management practices and the inherent financial stability provided by Shari’ah compliance. Conclusion. The study concludes that the Islamic economic system has strong potential to offer a sustainable and stable alternative in responding to global financial crises. With supportive regulations and public policies, the success and stability of Islamic finance can be further enhanced, contributing to broader economic resilience.